2013
DOI: 10.1104/pp.113.232884
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Jasmonate-Elicited Transcriptional Responses and Pentacyclic Triterpene Biosynthesis in Sweet Basil    

Abstract: Sweet basil (Ocimum basilicum) is well known for its diverse pharmacological properties and has been widely used in traditional medicine for the treatment of various ailments. Although a variety of secondary metabolites with potent biological activities are identified, our understanding of the biosynthetic pathways that produce them has remained largely incomplete. We studied transcriptional changes in sweet basil after methyl jasmonate (MeJA) treatment, which is considered an elicitor of secondary metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 84 publications
(128 reference statements)
4
103
0
Order By: Relevance
“…The concentration of MeJA partially determines whether genes are up-or down-regulated (Sun J.W. et al, 2013;Misra et al, 2014). In our study, some metabolic pathways were characterized by strong down-regulation due to 0.25 mmol/L MeJA.…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations
“…The concentration of MeJA partially determines whether genes are up-or down-regulated (Sun J.W. et al, 2013;Misra et al, 2014). In our study, some metabolic pathways were characterized by strong down-regulation due to 0.25 mmol/L MeJA.…”
Section: Discussionsupporting
confidence: 47%
“…3.3.6 Effect of MeJA on the terpenoid biosynthesis pathway Plant terpenoids, which play an important role in the basic life activities of plants, are increased by foliar applications of MeJA (Han et al, 2007;Chang et al, 2013;Misra et al, 2014). We found that genes involved in eight types of terpenoid biosynthesis pathways were induced.…”
Section: Effect Of Meja On the Vitamin Pathwaymentioning
confidence: 73%
See 2 more Smart Citations
“…ObAS1 was identified as a beta-amyrin synthase, whereas ObAS2 was a mixed amyrin synthase that produced both alpha-amyrin and beta-amyrin but had a product preference for alpha-amyrin. Moreover, transcript and metabolite analysis shed light on the spatiotemporal regulation of pentacyclic triterpene biosynthesis in sweet basil (Misra et al 2014).…”
Section: The Activation Of Key Enzymementioning
confidence: 99%